Factor Affecting Sarawak Consumer Adoption of Mobile Payment - Jong, Sing Hui (Universiti Malaysia Sarawak (UNIMAS), 2019)
The objective of this study is to identify the relationship between identified factor(s) (Performance expectancy, Effort expectancy, Social Influence and Facilitating Condition) and behavioural intention to adopt mobile payment as well as to identify the relationship between behavioural intention and Sarawak consumer adoption of mobile payment. The conceptual frameworks that are adopted in this study are Unified Theory of Acceptance and Use of Technology (UTAUT). There are total of 400 questionnaires are distributed through both web- based and paper- based questionnaires. Firstly, UTAUT constructs are developed based on past studies and the concept of each construct is being examined. Furthermore, the relationships between each of the construct are being examined as well. Followed by the examination of the validity and reliability of each of the measuring instruments. The findings of this study are all the constructs have relatively significant positive relationship on behavioural intention to adopt mobile payment. In addition, there is a positive relationship between behavioural intention and Sarawak consumer adoption of mobile payment.